Competing risks and deposit insurance governance convergence. Issue 2 (March 2014) - Gandrud, Christopher
Why do policies often seem to converge across countries at the same time? This question has been studied extensively in the diffusion literature. However, past research has not examined complex choice environments, especially where there are many alternatives. This article fills this gap in the literature. I show how Fine and Gray's Competing Risks Event History Analysis can be used to tease apart the causes of policy convergence. I apply the method to an examination of the reasons why, from the mid-1990s to 2007, many countries created independent deposit insurers. I find an interaction between international recommendations and regional peers' choices, particularly in the European Union. However, convergence appears to slow under the particular conditions of a banking crisis, regardless of how well independence is promoted. Possibly due to electoral incentives, democracies seem to have been more likely to create independent insurers. Ultimately, I demonstrate how competing risks analysis can help enable future research on policy choices, complementing methods previously applied in political economy.